Formulasi dan Evaluasi Sediaan Tablet Nanopartikel Ekstrak Daun Salam (Syzygium Polyanthum) dengan Variasi Konsentrasi Na Alginat dan Avicel PH 102 - Agung Setiawan; Naelaz Zukhruf Wakhidatul Kiromah; Tri Cahyani Widiastuti (Pharmacon: Jurnal Farmasi Indonesia, 2020)
The use of traditional medicines is an alternative treatment which is considered safer in terms of side effects and toxicity. One of the herbal plants that have properties that can reduce blood pressure is bay leaf (Syzigium polyanthum) because it contains essential oils (citral, eugenol), tannin, and flavonoids. Ethanol extract of bay leaves (Syzigium polyanthum) with antihypertensive potential needs to be made into dosage forms. This study aimed to determine the optimal formula of the preparation of bay leaf (Syzigium polyanthum) nanoparticles tablet with variations in the concentration of Na alginate and Avicel PH 102. Salam leaf extract was made using maceration method using  ethanol 96%, followed by evaporation until thick extract was formed. Colloidal nanoparticles were prepared by mixing bay leaf extract into  technical ethanol 96% and aquadest, chitosan solution in acetic acid and NaTTP solution. Further, it was measured using PSA (Particle Size Analyzer) to determine the particle size. Tablets were prepared using 4 formulas with variations in the concentration of sodium alginate and avicel PH 102 using the direct pressing method. The results of this study indicate that variations in the concentration of Na alginate and Avicel PH 102 affect the physical properties of tablets. The addition of Avicel PH 102 can increase the hardness and disintegration time of the tablet. While the addition of Na alginate can increase the fragility of tablets. Based on the evaluation results, the optimum formulation of tablet formulas is formula 4.